Legal Pluralism as a Method of Interpretation: A Methodological Approach to Decolonising Indigenous Peoples’ Land Rights under International Law - Perrin, Jonas (2017)
Ever since the arrival of the European colonisers, theories of international law have been used to justify the process of dispossession of indigenous lands. Even though the adoption of human rights have led to some amelioration, the author claims that this has proved unsatisfactory to address indigenous concerns for one reason: international law remains deeply rooted in colonial concepts, such as the concepts of ‘sovereignty’ and ‘property’. Given that these concepts clearly contradict indigenous cosmovisions, the author proposes a pluralist interpretation of indigenous land rights under international law. Understood as a method of interpretation, it is able to take into account not only ‘state law’ but also indigenous conceptions of the relationship between human beings and the land. It is thus proposed that such a methodological approach may decolonise colonial concepts of international law. //Desde la llegada de los colonizadores europeos, las teorías del derecho internacional han sido utilizadas para justificar el proceso de desposesión de las tierras indígenas. Aunque la adopción de derechos humanos ha conducido a una cierta mejora, el autor afirma que esto ha resultado insatisfactoriamente para abordar preocupaciones indígenas por una razón: el derecho internacional permanece profundamente arraigado en conceptos coloniales, tales como los conceptos de la “soberanía” y de la “propiedad”. Dado que estos conceptos se contradicen claramente con la cosmovisión indígena, el autor propone una interpretación pluralista de los derechos indígenas a sus tierras en el marco del derecho internacional. Como método de interpretación, tal planteamiento pluralista es capaz de no solo tomar en cuenta la “ley estatal,” sino también concepciones indígenas con respecto a la relación entre el ser humano y la tierra. Por lo tanto, el autor propone que tal planteamiento metodológico pueda descolonizar conceptos coloniales del derecho internacional.